Alleviation of soil acidification and modification of soil bacterial community by biochar derived from water hyacinth Eichhornia crassipes - Rumpa Jutakanoke; Nuttakorn Intaravicha; Purin Charoensuksai; Wuttichai Mhuantong; Jarungwit Boonnorat; Jirapast Sichaem; Wongsakorn Phongsopitanun; Warunya Chakritbudsabong; Sasitorn Rungarunlert (Scientific Reports, 2023)
Abstract The highly acid sulfate Rangsit soil series of Rangsit, Pathum-Thani district, Thailand poses a major problem for agriculture in the area. Water hyacinth is a naturally occurring weed that can grow aggressively, causing eutrophication and leading to many severe environmental impacts. Here, through the pyrolysis process, we convert water hyacinth to biochar and use it for acid soil amendment. We found the ratio between biochar, soil, and sand suitable for the cultivation of water convolvulus to be 50 g of biochar, 400 g of soil, and 100 g of sand (1:8:2). This soil mixture improved the pH of the soil from 4.73 to 7.57. The plant height of the water convolvulus grown in the soil mixture was the greatest at 20.45 cm and the plant weight with and without roots was greatest at 2.23 g and 2.52 g, respectively. Moreover, we demonstrated the dominance and high abundance of Bacillus among the community in soil with biochar amendment. Here we provide the first assessment of the appropriate amount of water hyacinth-derived biochar for mitigation of soil acidity and promotion of optimal water convolvulus growth. Moreover, biochar can optimally modify soil bacterial communities that benefit plant development.